PENGENDALIAN ABRASI PANTAI TUMPAAN, AMURANG, MINAHASA SELATAN, SULAWESI UTARA DENGAN MENGGUNAKAN PEGAR GEOBAG RANGKA BAMBU - Arif, Alisha Maharani Shivananda; Hamdi, Nashrul Fath (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2022)
Coastal abrasion is damage to the shoreline due to the detachment of beach material, such as sand or clay that is continuously hit by sea waves or due to changes in the balance of sediment transport in coastal waters. Coastal areas are transitional areas of the sea and land. These conditions cause coastal areas to get pressure from various activities and phenomena that occur on land and at sea. In Tumpaan beach, Amurang, Minahasa, North Sulawesi, abrasion has hit quite often for a long period of time. The condition of the sedimentary soil around the location is also one of the factors that can damage the coastal area. This study was conducted using a qualitative and descriptive approach. The research is limited to the causes of abrasion and its countermeasures using PEGAR geobags as well as the costs required for its construction. Geobags are sandbags made of superior non-woven polypropylene geotextile with high tensile strength designed to be resistant to abrasion, UV light, and also coblos (puncture).